An Assessment of Cultural Factors Affecting Insurance Uptake: A Survey of the Nairobi Central Business Districts - Gitau, Peter N.; Sile, Dr. Isabella (European Journal of Business and Strategic Management, 2016)
Purpose: the purpose of this study was to establish the effect of cultural factors that affect the uptake of insurance in Nairobi central business district, Kenya. Methodology: The study employed a descriptive research design. Primary data was used in the study and was gathered using a questionnaire. The target population for the study was the existing and potential insurance customers within the Nairobi CBD. The study targeted a population of 160 respondents and a sample of 100 respondents was chosen. The main sampling technique that was used for this study is stratified random sampling. Secondary data was collected from books, journals and the internet. The primary data was first coded and organized into themes, categories and patterns. Results: Based on the findings the study concluded that religion has a negative effect on the uptake of insurance in Kenya. Further, cultural taboos and beliefs, cultural attitudes and values language used by insurance sales agents, education have a negative effect on the uptake of insurance in Kenya. Unique contribution to theory, practice and policy: The study recommended that IRA should encourage insurance companies to sensitize the public on the different insurance products available in the market on a regular basis. The IRA and AKI should ensure that all the agents transacting the insurance business are properly trained, licensed and motivated to help reduce the perception that insurance agents are conmen or dishonest. The IRA should embark on a campaign to sensitize the public about the benefits of insurance in a bid to change their attitudes towards taking up insurance covers.